PERSEPSI DAN MINAT SISWA TERHADAP MATERI PELAJARAN SENI RUPA DI SMA NEGERI 1 GUNUNG TALANG - IKHWANUL FAJRI, Drs. Eswendi,M.Pd, Drs. Efrizal, M.Pd (Serupa The Journal of Art Education, 2014)
This reserach aimed to know how is students perception and interest toward the learning material of fine arts subject in SMA Negeri 1 Gunung Talang Kabupaten Solok. The research was ca descriptive quantitative research. The population of this research is all of students. The sample of this research is 251 students at X, XI, and XII class in SMA Negeri 1 Gunung Talang. To determined the sample, the researcher used formula r tabel on standard error 5%within stratifed propotioned random sampling technique. The result of this research in the filed has been found follows : 1) Students perception toward learning meterial of fine arts has been good (49,8%), 2) Students interest toward learning material of fine arts also good (34,7%).It means that students perception and interest toward learning material in fine arts subject at SMA Negeri 1 Gunung Talang has good.Kata Kunci: Persepsi, minat, materi pelajaran seni rupa